Falling Through the Cracks: The Current Gap in the Health Care Transition of Patients With Kawasaki Disease<subtitle>A Scientific Statement From the American Heart Association</subtitle> - Nagib Dahdah (Wiley, 2021)
Background Health care transition (HCT) is a period of high vulnerability for patients with chronic childhood diseases, particularly when patients shift from a pediatric to an adult care setting. An increasing number of patients with Kawasaki disease (KD) who develop medium and large coronary artery aneurysms (classified by the American Heart Association according to maximal internal coronary artery diameter Z‐scores ≥5 and ≥10, respectively) are becoming adults and thus undergoing an HCT. However, a poor transition to an adult provider represents a risk of loss to follow‐up, which can result in increasing morbidity and mortality. Methods and Results This scientific statement provides a summary of available literature and expert opinion pertaining to KD and HCT of children as they reach adulthood. The statement reviews the existing life‐long risks for patients with KD, explains current guidelines for long‐term care of patients with KD, and offers guidance on assessment and preparation of patients with KD for HCT. The key element to a successful HCT, enabling successful transition outcomes, is having a structured intervention that incorporates the components of planning, transfer, and integration into adult care. This structured intervention can be accomplished by using the Six Core Elements approach that is recommended by the American Academy of Pediatrics, the American Academy of Family Physicians, and the American College of Physicians. Conclusions Formal HCT programs for patients with KD who develop aneurysms should be established to ensure a smooth transition with uninterrupted medical care as these youths become adults.